Sideways stories from Wayside School - Sachar, Louis, 1954-; Heitz, Tim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
Humorous episodes from the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.
"Ages 8-12"--Back cover.
3.9
3-6.
3-6
Keywords: Humorous stories; Schools -- Juvenile fiction; Humorous stories; Schools -- Fiction; Humorous fiction; School stories; Humorous fiction; School fiction